2022
DOI: 10.3390/ijerph192013145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Intervention to Promote Self-Management Regarding Cardiovascular Disease: The Social Engagement Framework for Addressing the Chronic-Disease-Challenge (SEFAC)

Abstract: Background: Cardiovascular diseases (CVD) are predominantly lifestyle related. Mental health issues also influence CVD progression and quality of life. Self-management of lifestyle behaviors and mental well-being may play a significant role in reducing the CVD burden. Previous studies have shown that mindfulness practices are associated with psychological well-being, but their effects on CVD self-management are mainly unknown. Methods: The study had a before–after design and included adults over 50 years with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(47 reference statements)
1
2
0
Order By: Relevance
“… 38 General self-efficacy is an essential belief factor in self-management, that is, the stronger the sense of general self-efficacy, the stronger the confidence in disease management. 53 Serial multiple mediation models have demonstrated that e-health literacy and general self-efficacy serially mediate the relationship between social support and self-management, thus supporting Hypothesis 4, which has similarities and differences with the findings of previous studies. 39 , 54 To fully encourage patients’ behavioral motivation and achieve self-empowerment, the use of e-health literacy to increase patients’ self-management ability should also pay more attention to patients’ general self-efficacy.…”
Section: Discussionsupporting
confidence: 64%
“… 38 General self-efficacy is an essential belief factor in self-management, that is, the stronger the sense of general self-efficacy, the stronger the confidence in disease management. 53 Serial multiple mediation models have demonstrated that e-health literacy and general self-efficacy serially mediate the relationship between social support and self-management, thus supporting Hypothesis 4, which has similarities and differences with the findings of previous studies. 39 , 54 To fully encourage patients’ behavioral motivation and achieve self-empowerment, the use of e-health literacy to increase patients’ self-management ability should also pay more attention to patients’ general self-efficacy.…”
Section: Discussionsupporting
confidence: 64%
“…While there is a widespread belief in the importance of self-management programs for improving health behaviors in people with chronic conditions (10,52,53), the present study failed to show the effects of a well-established CDSMP on health behaviors. A recent study of a comparable CDSMP also reported no effect on health behaviors (54). Similarly, a meta-analysis and systematic review of self-management intervention studies showed improvement in subjective wellbeing, but overall, there were no effects on physical activity, diet and nutrition, smoking, alcohol consumption, and blood pressure (55,56).…”
Section: Discussionmentioning
confidence: 97%
“…In a survey regarding smoking cessation among cardiac patients, it was found that self-efficacy is a good predictor of the intention to quit smoking and indirectly mediates abstinence [ 43 ]. The findings suggest that self-efficacy plays a critical role in reducing smoking rates, particularly in challenging circumstances such as social events or exposure to smoking peers [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%